Filiation and Assisted Reproductive Technology - Corral, Hernán (Revue générale de droit, 2001)
This article deals with the various filiation issues arising from the application of assisted reproduction techniques. The author asserts that assisted reproduction techniques produce a dissociation between the blood and genetic elements of procreation and people's will to become parents, which causes hard judicial dilemma in paternity suits. Legislative and judicial criteria developed both under European and American legal systems to solve this case are systematized in the article, wherein the author directs criticism to those criteria that tend to undermine the natural physiology of human reproduction in spite of the "intent of reproduction" concept. This latest concept is criticized as being a form of contractualization of filiation links. The author suggests that a deeper understanding of the human dignity, and of the international standard of the best interest of the child should be useful to protect children from being a part of the new market-of-human-beings that could arise from the massive application of assisted reproduction techniques.